Analysis of storage quality of crayfish (Procambarus clarkii) meat based on sous-vide cooking - ZHAO, Qing; LI , Hailan; CAI, Jun; LIAO, Tao; QIU, Liang; ZU, Xiaoyan (Food Science and Technology, 2023)
This study aimed to investigate the effect of different combinations of temperature and time of sous-vide (SV) on the quality of crayfish (Procambarus clarkii) meat. The changes in quality indexes and volatile components of crayfish meat after SV treatment were analyzed after refrigeration at 4°C for 1–7 days. The L* values of crayfish meat were higher in the SV group than in the control group (p<0.05). Heating at 75℃ effectively suppressed the decrease in hardness and increase in total volatile basic nitrogen (TVB-N) and total viable count (TVC) of crayfish meat (p<0.05). A heating time of 15 min was optimal for most of the indicators. TVB-N, thiobarbituric acid, and TVC were positively correlated with each other and negatively correlated with hardness. Using GC-MS, 59 volatile compounds were identified with a match of >85%. During storage, the highest percentages of volatile alkanes and aromatic hydrocarbons were 44.57 and 14.81%, respectively, with 33 species of aromatic hydrocarbons being identified. In conclusion, SV treatment with a heating temperature of 75℃ and heating time of 15 min improved the texture and flavor quality of crayfish meat during storage.